Bureaucracy and innovation: the entrepreneurial state - Kattel, Rainer (Henry Stewart Talks, 2023)
Target audience, Bureaucracy, Innovation, Entrepreneurial state, Climate emergency, Government, Democracy, Goal setting and implementation, Accountability, Diversity